2023
DOI: 10.3389/fspas.2023.1198071
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of FORMOSAT-3/COSMIC radio occultation and ionosonde measurements in sporadic E detection over mid- and low-latitude regions

Abstract: The investigation of sporadic E or Es layers typically relies on ground-based or satellite data. This study compares the Es layers recorded in ionograms with those detected using GNSS L1 signal-to-noise ratio data from FORMOSAT-3/COSMIC radio occultation at mid and low latitudes. GPS radio occultation measurements of Es layers, during an 11-year time span of 2007–2017, within a 2° latitude × 5° longitude grid around each ionosonde site are compared to the Es recordings of the ionosonde. By comparing multi-year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 40 publications
1
2
0
Order By: Relevance
“…In addition, both models perform better for daytime measurements with slight overpredictions of weak nighttime intensities. The increased daytime performance is consistent with a recent study by Sobhkhiz-Miandehi et al (2023), which found a stronger agreement between ionosonde and RO measurements during the day with low solar zenith angles.…”
Section: Model Performancesupporting
confidence: 91%
See 1 more Smart Citation
“…In addition, both models perform better for daytime measurements with slight overpredictions of weak nighttime intensities. The increased daytime performance is consistent with a recent study by Sobhkhiz-Miandehi et al (2023), which found a stronger agreement between ionosonde and RO measurements during the day with low solar zenith angles.…”
Section: Model Performancesupporting
confidence: 91%
“…In addition, small-scale structures and turbulence caused by Kelvin-Helmholtz instabilities (Bernhardt, 2002;Hysell et al, 2016) can create significant changes in GNSS-RO observations [also discussed in Emmons et al (2022)]. Finally, a recent comparison of ionosonde with RO observations found the best agreement during the day of local summer and also noted that certain ionosonde sites systematically showed stronger agreement with RO E s observations (Sobhkhiz-Miandehi et al, 2023). This site-to-site and temporal variation is the result of site-dependent ionosonde hardware, background ionosphere fluctuations, and perhaps a geographic and temporal dependence of E s spatial characteristics and small-scale structures, which should be examined in more detail in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…The use of h′Es instead of hEs has been applied in many sporadic E studies. Among others, these include: (a) several Es diurnal and seasonal variability investigations (e.g., see a recent paper by Haldoupis et al (2023) and more references therein), (b) "Height Time Intensity" (HTI) studies of tidal periodicities and altitude descent of sporadic E layers (e.g., see Haldoupis et al, 2006; and a review paper by Haldoupis (2012)), (c) comparison studies of Es altitudes measured independently by satellite GPS (Global Positioning System) radio occultation (RO) methods and ionosondes (e.g., see Arras, 2010;Ellis et al, 2024;Gan et al, 2022;Resende et al, 2018;Sobhkhiz-Miandehi et al, 2023, and several more references), and (d) the computation of foμEs, which is an ionogram-based parameter for measuring Es metal ion densities and thus the associated layer intensities (Ellis et al, 2024;Emmons et al, 2023;Haldoupis, 2019;Haldoupis et al, 2020). Therefore, the convenient adoption of hEs being equal to h′Es should have caused inaccuracies in past studies.…”
Section: Introductionmentioning
confidence: 99%